IMPACT OF CLUSTER IONS AND AIR POLLUTION ON HUMAN HEALTH (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Maximum permissible concentration of polluting substances in the atmospheric air is defined in the laws and regulations of many countries. The concentration of cluster ions from 400 to 3000 ions per m3 is generally considered to be appropriate for human health. The author of this article analyses potential cases when air enrichment with air ions could enhance air purification and influence favourably human health. The author also describes possible adverse effects when air ionisation can increase the harmful impact on human body, especially in situations when the concentration of polluting substances exceeds the maximum permissible level.